Characteristics of personality and assertiveness in students of the Faculty of Health Sciences - Bermúdez Vargas, Katterin (2019)
Objective: To determine the relationship between the personality traits and the assertiveness in 210 students ofboth sexes, between 16 and 25 years of age of the first and second year of the Faculty of Health Sciences of aprivate University of East Lima. Materials and Methods: This was a non-experimental, quantitative, descriptive,correlational study. Five-Factor Personality Inventory (NEOFFI) and the Assertiveness Assessment Scale(ADCA-1) were used. Results: The results showed that there is a significant relationship between the variables.Thus, a highly significant relationship was found between the neuroticism trait with self-assertiveness (r = -0.449p = 0.000) and with heteroartivity (r = -0.292 p = 0.000). In addition, there is a highly significant relationshipbetween the extraversion feature with self-assertiveness (r = 0.391 p = 0.000) and heteroartivity (r = 0.198 p =0.004). Conclusions: Finally, a highly significant relationship was found between the self-assertive responsibility(r = 0.447 p = 0.000) and heteroartivity (r = 0.238 p = 0.001) among university students.